THE ANALYSIS ON THE STAKEHOLDERS OF CONFLICT MITIGATION IN THE WAY KAMBAS NATIONAL PARK, LAMPUNG - Andyono, Gebyar; Marsono, Djoko; Sadono, Ronggo; Imron, M Ali (KINERJA, 2018)
Stakeholders with different interests and influences (power) are related to the human-wild elephant conflict mitigation in the Way Kambas National Park in Lampung. Stakeholders need to manage properly to achieve conflict mitigation objectives optimally. This research was conducted in Way Kambas National Park in Lampung. Data were collected with observations, interviews, and related document studies without involving active participations of related stakeholders and data were analyzed by using descriptive qualitative analysis. This research was conducted from September to December 2016. The identification results showed that there were 11 stakeholders dealing with the human-wild elephant conflict mitigation in Way Kambas National Park. The identified stakeholders were divided into three classifications: (1) subject stakeholders coming from farmer groups and people from buffering villages, (2) key player stakeholders consisting of Way Kambas National Park Institution, regional government (village, district and provincial governments), local partners/non-government organizations (Sumatra Forest Conservation and Wildlife Conservation Society-Indonesia Program), Forum Rembug Desa Penyangga/village discussion forums, and Lampung University, and (3) the context setter stakeholder from a private company (PT. Nusantara Tropical Fruit). This research did not find stakeholder from crowd classification. The relationships between stakeholders showed complementary cooperation. The implication of human-wild elephant conflict mitigation management in Way Kambas National Park is that the stakeholder management to build cooperation and collaboration in the form of communication forums to achieve the objectives of human-wild elephant conflict mitigation in Way Kambas National Park is required.Keywords: stakeholder, power-interest matrix, actor-linkage matrix, Way Kambas National Park